2018
DOI: 10.1111/itor.12537
|View full text |Cite
|
Sign up to set email alerts
|

Quality spillover, tariff, and multinational firms' local sourcing strategies

Abstract: It is prevalent for multinational firms (MNFs) to enter a market by importing products of superior quality, and then engage in local competition with domestic manufacturers (DMs). Alternatively, many MNFs voluntarily expose themselves to the risk of quality spillover by strategically sourcing from DMs to avoid the tariff burden. In this paper, we consider a DM and an MNF that strategically choose whether to source from the DM, and characterize the tradeoff between the tariff burden and the potential loss due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Contrary to the effect of tariff increase, Fan et al [4] pointed out that tariff reduction is beneficial to export enterprises through reduced marginal production costs. Niu et al [5] showed that tariffs imposed by importing countries increase the procurement costs of domestic multinational corporations and reduce the procurement volumes of multinational corporations. Rong and Xu [6] assessed the impact of manufacturer altruistic preferences and government subsidies on the multinational green supply chain under dynamic tariffs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contrary to the effect of tariff increase, Fan et al [4] pointed out that tariff reduction is beneficial to export enterprises through reduced marginal production costs. Niu et al [5] showed that tariffs imposed by importing countries increase the procurement costs of domestic multinational corporations and reduce the procurement volumes of multinational corporations. Rong and Xu [6] assessed the impact of manufacturer altruistic preferences and government subsidies on the multinational green supply chain under dynamic tariffs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many multinationals move their business to low-tax countries due to cost pressures, Wu and Lu [35] study the effectiveness of the cost-plus or resale price approach to improve multinational earnings. To lower the procurement cost of raw materials, Niu et al [26] investigate the risk of technology spillovers from the local sourcing implemented by the MNMs in a tariff increase setting and confirm that the benefits to the MNMs and the local manufacturers would increase when the risk is low. Many famous raw material suppliers have begun to operate their brand products for more revenue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the entry of large-scale green products into emerging markets helps countries to achieve sustainable development goals [67], the MNMs in emerging markets will face challenges [26,68]. For example, the local manufacturers will compete for the market with a large quantity of low-cost regular goods.…”
Section: Problem Description and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Niu et al. (2019d) consider a co‐opetitive supply chain where a multinational firm (MNF) strategically sources from a domestic manufacturer when the latter is the MNF's local competitor. Huang et al.…”
Section: Literature Reviewmentioning
confidence: 99%